Feasibility of lowering-in of longitudinally continuous cold-bends - Yanbing WANG; Tong SHI; Haichun LIU; Yihua ZHAO; Qinlong DONG; Shengyi SHA; Mingzhe BU; Hong ZHANG; Hao WANG (You-qi chuyun)
Objective Lowering-in is a primary method for underground pipeline laying. Continuous cold bends are utilized in place of hot-bending elbows at longitudinal turns along these buried pipelines. In this context, the maximum stress in the pipelines is considered a critical indicator for assessing safety when lowering longitudinally continuous cold bends into the trenches. Methods Taking X80 pipes with a diameter of 1 219 mm and wall thickness of 22 mm as an example, the Finite Element Method (FEM) was used to establish a numerical model for the lowering-in process of longitudinally continuous cold bends into the trench. The subsequent analysis focused on investigating the stress variations in the pipeline throughout the lowering-in process, aimed to discuss the impact of different factors such as lowering depth, angle of continuous cold bends, and the direction of trench excavation on pipeline stress levels. Results The presence of continuous cold bends resulted in an elevation of the maximum stress in the pipeline during the lowering-in operation, and the maximum stress was found near the initial boundary of the cold bends. In the lowering-in process, the pipeline's maximum stress was identified as compressive stress on the uphill and tensile stress on the downhill, with nearly identical absolute values at equivalent gradients. Trench excavation from a slope transitioning into a level section caused an escalation in the pipeline's maximum stress, directly correlating with increased lowering depths and angles of continuous cold bends. The stress calculations for longitudinal continuous cold bends constructed from X80 pipes with a diameter of 1 219 mm and wall thickness of 22 mm during the lowering-in process demonstrated that, at a turning angle of 26° and a lowering depth of 5 m, the resultant maximum stress in the pipeline complied with the established requirements for the lowering-in of oil and gas transmission pipelines. The implementation of layered excavation within a 100 m range preceding and following the cold bends was identified as an effective measure for managing pipeline stress levels. Conclusion Pipeline stress is influenced by multiple parameters during the lowering-in process. By analyzing the trends in maximum stress variation in this process, effective control measures can be employed to streamline the lowering-in of continuous cold bends at longitudinal pipeline turns.